Inclusive growth and health - James, Chris (OECD Publishing, 2017)
In response to observed growing inequalities in income and other dimensions of well-being, including health, the OECD launched an initiative on Inclusive Growth in 2012. The objective was to help governments find ways to make economic growth more inclusive, so that it translates into meaningful gains in living standards across key dimensions of well-being and different socioeconomic groups. This paper links health to the overall inclusive growth agenda. It assesses the two-way relationship between health and socioeconomic factors. An empirical health production function is specified, using data from 35 OECD countries for the period 1990-2015. This is complemented by a review of the related empirical literature, as well as successful policies across OECD countries
Keywords: Social Issues/Migration/Health